Review on epidemiology, milk composition changes, and antimicrobial susceptibility of causative agents of Bubaline mastitis in Asia - Mohd Amin, Nor’Amira; Abu Bakar, Md Zuki; Omar, Sharina; Mansor, Rozaihan (Universiti Putra Malaysia, 2023)
Mastitis is one of the diseases that cause economic losses worldwide due to the reduction in milk yield and the high treatment costs in dairy buffaloes. Although antibiotics are the mainstay treatment for this disease, the overuse of antibiotics has resulted in the emergence of antimicrobial resistance in animals and humans. Hence, this study aims to review and assess the available literature on bubaline mastitis in Asia. The prevalence of subclinical mastitis was higher in dairy buffaloes than in clinical mastitis, especially in Pakistan. Bubaline mastitis was commonly detected using the California mastitis test, surf field mastitis test, somatic cell count, and bacterial culture. In Asia, farm management and host factors were the primary causes of bubaline mastitis risk factors. Mastitis in buffaloes caused alterations in milk composition, such as increasing lactose levels, somatic cell count, and the presence of bacteria in the milk. However, protein, fat, and solid non-fat level variations were also affected by other factors such as the stage of lactation, breed, and age. The most prevalent isolated bacteria in bubaline mastitis milk samples were coagulase-negative staphylococci, Staphylococcus aureus, Streptococcus spp., and Escherichia coli. Most showed high resistance toward penicillin, amoxicillin, ampicillin, and streptomycin. The antimicrobial susceptibility of causative agents in Asia varies depending on the usage of common antibiotics to treat bubaline mastitis in each country. This review will help to understand bubaline mastitis better, although studies are limited in many Asian countries.